El saber de las madres gestantes sobre estimulación prenatal en Trujillo - Marín Campos, Ethel Ivonne (2015)
This qualitative study was to study the subject of "Knowledge of pregnant women about prenatal stimulation” The method used was the creative and sensitive, theorized and implemented by Cabral (1998) the stage was Trujillo district. With 10 participants. The techniques used were: group interview, group discussion and participant observation, associated with critical pedagogy reflective of Freire (2000), based on dialogue, themes to encode, decode and recode sub synthesis in two analytical categories: 1) Prenatal stimulation for good growth and development of children comprising the love and happiness that transmits the pregnant mother to the baby and mother care with good nutrition and education in their prenatal checkups, 2) Prenatal stimulation for the child's socialization with communication of the pregnant mother with her baby: Talking, caress and singing and music for the intellectual, creative and social development of children. Whereas the study at any time, scientific rigor and ethical criteria.